Reactivity-based identification of oxygen containing functional groups of chemicals applied as potential classifier in non-target analysis - Milena Latz; Alexander Böhme; Nadin Ulrich (Scientific Reports, 2023)
Abstract In this work, we developed a reactivity-based strategy to identify functional groups of unknown analytes, which can be applied as classifier in non-target analysis with gas chromatography. The aim of this strategy is to reduce the number of potential candidate structures generated for a molecular formula determined by high resolution mass spectrometry. We selected an example of 18 isomers with the molecular formula C12H10O2 to test the performance of different derivatization reagents, whereas our aim was to select mild and fast reaction conditions. Based on the results for the isomers, we developed a four-step workflow for the identification of functional groups containing oxygen.